Smart In-Cabin Air Monitoring System using IoT Technologies - Falah Y H Ahmed; Jabar H. Yousif; Marwan Alshar’e; Maram El Sheikh; Ehsan Al-Ajmi; Mahmood Al-Bahri (Qubahan Academic Journal)
This research develops a monitoring system that improves the safety of people in the car. Continuous monitoring of in-cabin air quality is an important step in achieving a safer environment inside the cabin. Using oxygen, carbon dioxide, and temperature sensors to monitor those variables at all times, combining them with an Arduino to process those variables. In the event of approaching danger levels, a message is generated and sent to the owner of the car alerting them of the changes in the variables. This step allows the owner to resolve the situation without compromising the security of the vehicle. If the readings continue to depreciate, the Arduino will roll down the windows slightly allowing fresh air into the cabin, message the driver again to inform them of the action taken and alert the authorities to act immediately in case medical assistance is required. Cars have become the most common means of transportation in the world. While car crashes are looked at as the source of deaths related to vehicles, lack of oxygen and cabin overheating-related deaths have been rising. Many scenarios can lead to deaths in a stationary car such as children being left inside a car alone, parents unintentionally leaving their children in the back seats while rushing to work in the morning, and napping or sleeping in the car. Those scenarios are dangerous because of the effect of low oxygen, high carbon dioxide, and high temperature on humans. Oxygen deprivation and high carbon dioxide intake negatively affect the human brain.